Influence of spacer filament fineness on indentation characterizations of warp-knitted spacer fabrics for mattresses. (November 2022) - Qu, Mingyue; Xia, Fenglin; Fang, Fangfang; Huang, Lili; Ma, Pibo
Mattress plays an important role in the quality of human sleep, warp-knitted spacer fabric (WKSF) is a rather important mattress material, this paper explored the indentation state of WKSFs of 20 mm thickness and 0.12, 0.15, 0.18, and 0.25 mm spacer filaments under the action of curved surface pressure by using spherical compression tests and finite element simulations, with the combination of three-dimensional and non-uniform pressure characteristics exerted on the mattress by the human body when lying down. Tests and simulations analysis would be shown in four aspects: firstly, when the spherical indenter acts on the WKSFs, the compressive stress, Indentation Force Deflection (IFD) and support factor (SF) of the WKSFs increase as the spacer filament fineness increases; secondly, the compression depth of WKSFs should be controlled within 40% when used as mattresses to obtain good compression comfort; thirdly, A warp-knitted spacer fabric with a 0.25 mm spacer filament fineness provides both comfort and pressure resistance and better meets the needs of most people for a spacer fabric for mattresses.